2018
DOI: 10.1039/c8ta03075h
|View full text |Cite
|
Sign up to set email alerts
|

Unique Li4Ti5O12/TiO2 multilayer arrays with advanced surface lithium storage capability

Abstract: Unique Li4Ti5O12/TiO2 multilayer arrays from a substrate-free method demonstrate advanced surface lithium storage capability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…[ 1–3 ] Commercial graphite with low specific capacity (372 mAh g –1 ) and low lithiation potential (0.1 V vs Li + /Li) is difficult to meet the requirements of fast‐charging anodes. Although Li 4 Ti 5 O 12 is considered as a promising alternative to graphite anode, the energy density of Li 4 Ti 5 O 12 is severely limited by its low theoretical specific capacity (175 mAh g –1 ) and high lithiation potential (1.5 V vs Li + /Li) [ 4–7 ] . Low lithiation potential (0.2 V vs Li + /Li) of silicon anode with the highest specific capacity (3579 mAh g –1 ) could inevitably result in serious lithium dendrites in fast charging process.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] Commercial graphite with low specific capacity (372 mAh g –1 ) and low lithiation potential (0.1 V vs Li + /Li) is difficult to meet the requirements of fast‐charging anodes. Although Li 4 Ti 5 O 12 is considered as a promising alternative to graphite anode, the energy density of Li 4 Ti 5 O 12 is severely limited by its low theoretical specific capacity (175 mAh g –1 ) and high lithiation potential (1.5 V vs Li + /Li) [ 4–7 ] . Low lithiation potential (0.2 V vs Li + /Li) of silicon anode with the highest specific capacity (3579 mAh g –1 ) could inevitably result in serious lithium dendrites in fast charging process.…”
Section: Introductionmentioning
confidence: 99%
“…Within this context, considerable efforts have been dedicated in developing earth-abundant transition-metal-based and metal-free catalysts, among which carbon-based nanomaterials, containing carbon nanotubes, porous carbons and graphene, have been emerging as promising electrocatalysts owing to the distinct advantages of low cost, long-term stability, tunable surface properties, and sufficient electron conductivity [9][10][11][12][13][14]. Furthermore, doping heteroatom (e.g., N, P, B, S) into carbon frameworks can significantly improve the catalytic activity of carbon materials, as the dopant atoms can break the electroneutrality of nearby carbons and thus create the active sites, favoring the adsorption of O2 molecules and the subsequent oxygen reduction process [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Dey et al reported that coral-like NiO nanostructures were prepared by a facile hydrothermal technique, the response of the NiO sensor was found to be 292% in the presence of 190 ppm formaldehyde at 300 °C . In addition, the three-dimensional (3D) hierarchical structure has a higher specific surface area and faster gas diffusion rate than the conventional one-dimensional or two-dimensional (2D) structure. Ma et al synthesized a photocatalyst of hierarchically mesoporous titanium phosphonate by a hydrothermal method and it exhibited a significantly improved photocatalytic hydrogen evolution rate . Cao et al reported that the gas-sensing properties of the flower-like NiO structures are superior to the needle-like NiO structures on the basis of the research .…”
Section: Introductionmentioning
confidence: 99%